2017
DOI: 10.1038/mi.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for IL-22 in protection during chronic Mycobacterium tuberculosis HN878 infection

Abstract: Approximately 2 billion people are infected with Mycobacterium tuberculosis (Mtb), resulting in 1.4 million deaths every year. Among Mtb-infected individuals, clinical isolates belonging to the W-Beijing lineage are increasingly prevalent, associated with drug resistance, and cause severe disease immunopathology in animal models. Therefore, it is exceedingly important to identify the immune mechanisms that mediate protection against rapidly emerging Mtb strains, such as W-Beijing lineage. IL-22 is a member of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 44 publications
1
100
0
Order By: Relevance
“…IL-22 is a tightly regulated pro-and anti-inflammatory member of the IL-10 family that signals through the IL-22 receptors, and is composed of a ubiquitous IL-10R2 subunit and a restrictively expressed IL-22R1 subunit [29,48]. Even though the primary role of immune cells, especially Th cells, is the production of IL-22, it is well-known that several immune cells can induce IL-22R1 under certain pathologic conditions such as mycobacterium infected macrophages [49,50] and leukemia [51]. Hence, it is perhaps unsurprising to find that IL-22R1 is expressed in certain mononuclear cell population in obese conditions.…”
Section: Discussionmentioning
confidence: 99%
“…IL-22 is a tightly regulated pro-and anti-inflammatory member of the IL-10 family that signals through the IL-22 receptors, and is composed of a ubiquitous IL-10R2 subunit and a restrictively expressed IL-22R1 subunit [29,48]. Even though the primary role of immune cells, especially Th cells, is the production of IL-22, it is well-known that several immune cells can induce IL-22R1 under certain pathologic conditions such as mycobacterium infected macrophages [49,50] and leukemia [51]. Hence, it is perhaps unsurprising to find that IL-22R1 is expressed in certain mononuclear cell population in obese conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They appear to be the most abundant ILC group in the human lung, 62 but studies highlighting the role of ILC3s in the lung are limited. 82 Both IL-22 and IL-17 are important in protecting mice from hypervirulent strains of M tuberculosis, 85,86 and IL-22 from CD3 À CD56 + ILC3-like cells inhibits M. tuberculosis growth through enhanced phagolysosomal fusion. 81 ILC3s are in fact the major producers of IL-22 in the lung, 82,83 and consequently are probably important for tissue repair following viral infection.…”
Section: Ilc3smentioning
confidence: 99%
“…Indeed, boosting of IL-22 production by exogenous administration of flagellin allowed mice to clear an otherwise lethal infection. 82 Both IL-22 and IL-17 are important in protecting mice from hypervirulent strains of M tuberculosis, 85,86 and IL-22 from CD3 À CD56 + ILC3-like cells inhibits M. tuberculosis growth through enhanced phagolysosomal fusion. 87 Consistent with this, we recently showed that ILC3s play an important role in the immune response to M. tuberculosis infection.…”
Section: Ilc3smentioning
confidence: 99%
“…Elnaggar et al 42 Kathamuthu et al 43 Wang et al 44 Mayer-Barber et al 45 Mayer-Barber Hu et al 47 Wozniak et al 48 Ahmed et al 49 Pereira et al 50 Heidarnezhad et al 51 You et al 52 Wang et al 53 Xu et al 54 Zhao et al 55 Gopal et al 56 Treerat et al 57…”
Section: Do Classical Th1 Cytokines Represent the True Functional Sigmentioning
confidence: 99%